Working-Class Readers and Literary Culture in North-East England: The Allendale Lead-Miners’ Libraries - Kirstie Blair (Cahiers Victoriens et Edouardiens)
This article investigates the surviving borrowers’ catalogues (c.1850–70) of the Allendale lead-miners’ libraries, situating these within the wider history of workplace libraries in the North-East of England. It considers popular reading habits in this community and the patterns of borrowing among individuals, suggesting that these give us insight into the way in which working-class readers used libraries, especially those founded through management initiatives, and their reading preferences in the mid-Victorian period.